PENGARUH KEMAMPUAN TEKNOLOGI GURU TERHADAP KINERJA GURU MATEMATIKA DI ERA REVOLUSI INDUSTRI. MOTIVASI DAN LINGKUNGAN SEBAGAI MEDIASI - Habibullah; Elsa Desprina (UIR PRESS, 2021)
This study aims to describe the effect of the ability of mathematics teachers on teacher performance which is mediated by work motivation and work environment variables. This research was quantitative research with a correlational approach. The population was all mathematics teachers in Pekanbaru City. The sample was partly mathematics teachers who are taken by accidental technique. The accidental technique was chosen because during the COVID-19 pandemic it was not possible to collect data directly. Data retrieval is done only with a Google form and filled in by teachers who can use technology well. Sampling only distributed the instrument in the Google form to a group of elementary school teachers in Pekanbaru City. Data analysis using the path analysis approach. The results of the analysis show that there is a significant effect of technological ability on teacher performance in the Industrial Revolution 4.0 era through work motivation and the teacher's work environment. The results of the analysis are evidenced by a T-value greater than 1.96.